yCD/HPyCD Mixtures as Solubilizer: Solid-State Characterization and Sample Dexamethasone Eye Drop Suspension - Phatsawee Jansook; Garnpimol C. Ritthidej; Haruhisa Ueda; Einar Stefánsson; Thorsteinn Loftsson (Frontiers Media S.A., 2010)
Purpose. Study the complexation of dexamethasone in combinations of y-cyclodextrin (yCD) and 2-hydroxypropyl-y-cyclodextrin (HPyCD) with emphasis on solid characterization and development of aqueous dexamethasone eye drop suspension for drug delivery through sclera. Methods. Dexamethasone/cyclodextrin (dexamethasone/CD) solid complex systems were prepared and characterized by Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), X-ray diffractometry (XRD), and by in vitro drug dissolution testing. Sample eye drop suspensions were prepared applying solubilizer/suspender consisting of yCD/HPyCD mixtures, poloxamer 407 (P407) and polyvinylpyrrolidone. The eye drop suspension was characterized by its physicochemical properties. Results. The solid characterization techniques applied suggested that solid complexes were being formed. The results indicated that dexamethasone formed non-inclusion or micelle-like aggregates with HPyCD and the yCD/HPyCD mixture. The dissolution and dexamethasone release from the solid dexamethasone/yCD/HPyCD complexes was much faster than from the solid dexamethasone/yCD and dexamethasone/HPyCD complexes. The diameter of the solid particles in the dexamethasone eye drop suspension formulations were in all cases less than 10 μm with a mean diameter from 2.5 to 5.8 μm. The particle size decreased with increasing amount of P407. Permeation studies through semi-permeable membrane and porcine sclera showed that increasing the amount HPyCD could enhance drug transport through the membrane barriers and this was related to enhanced drug solubility. The permeation rates were, however, decreased compared to formulation containing yCD alone due to larger hydrodynamic diameter of dexamethasone/yCD/HPyCD complex aggregates. All formulations were both chemically stable for at least 8 months at 25oC and 40oC. Conclusions. Combination of yCD and HPyCD, i.e., formation of dexamethasone/yCD/HPyCD complexes, resulted in synergistic effect. That is the mixture had greater solubilizing effect than the individual CD, resulted in enhanced dissolution and drug delivery through membranes. Furthermore, it is possible to control the drug release rate by adjusting the yCD:HPyCD ratio in the solid dexamethasone/yCD/HPyCD complexes.